2020
DOI: 10.1155/2020/7958362
|View full text |Cite
|
Sign up to set email alerts
|

Construction of circRNA-Associated ceRNA Network Reveals Novel Biomarkers for Esophageal Cancer

Abstract: Objective. Esophageal cancer (ESCC) is reported to be the eighth most common malignant tumors worldwide with high mortality. However, the functions of majority circRNAs in ESCC requires to be further explored. Methods. This study identified differently expressed circRNAs in 3 paired ESCC using RNA-sequencing method. The interactions among circRNAs, miRNAs, and mRNAs were predicted using bioinformatics analysis. Results. In this study, using RNA-sequencing method and integrated bioinformatics analysis, 418 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…19,20 Studies have also demonstrated that the imbalance of circRNA levels exerts essential function in regulating EC development. 8,21 However, the effects of circFIG 4 on EC development have not been investigated. Here, we attested that circFIG 4 level was enhanced in EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Studies have also demonstrated that the imbalance of circRNA levels exerts essential function in regulating EC development. 8,21 However, the effects of circFIG 4 on EC development have not been investigated. Here, we attested that circFIG 4 level was enhanced in EC.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In recent years, diverse cir-cRNAs have been illuminated to be abnormally expressed in tumors and linked to the pathogenesis of human cancers by interacting with microRNAs (miRNAs), 7 including EC. 8 For example, circ-PRMT5 promoted the metastasis of EC by binding to miR-203. 9 circFIG 4 (also termed as hsa_circ_0077607), derived from FIG 4 precursor mRNA, was located at chr6: 110036280-110 064 975.…”
Section: Introductionmentioning
confidence: 99%
“…2 Pivotal players of ESCC pathogenesis, including proteins and circular RNAs (circRNAs), are being intensively explored. [3][4][5] Knowing the functions of these players may contribute to developing targeted and personalized therapy in further medicine.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recently, circRNAs have established roles via their ceRNA activity in impacting the establishment and progression of human tumors, 9 including ESCC. 4,5,10 Human circ_0001946 is originated in a process called back-splicing of exons of cerebellar degeneration related protein 1 (CDR1) and it has established a contradictory role in tumor biology. [11][12][13] Circ_0001946 is present at low levels in glioblastoma and lung cancer and it operates as a potential anti-tumor factor in these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Regarding ESCC, as well as other cancers, circRNAs with the potential to serve as novel biomarkers have been examined in recent years and their number is increasing. [10][11][12][13][14][15][16] Circular FAT1 (circFAT1, circ_0001461) is a noncoding RNA with a cyclic structure that is formed by the back-splicing of exon 2 of the FAT1 gene and head-to-tail binding. Its expression and oncological significance were initially reported for osteosarcoma in 2018 17 and subsequent studies reported similar findings for other cancer types.…”
mentioning
confidence: 99%